2003
DOI: 10.1111/j.0020-7985.2003.00260.x
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Immigration from Fiji to New Zealand: An Empirical Reassessment using the Bounds Testing Approach

Abstract: This article re-examines Gani's (1998) findings on the determinants of migrant flows from Fiji to New Zealand by employing the bounds testing procedure to cointegration, within an autoregressive distributive lag framework. The main findings are that in the long run all variables are statistically insignificant, although correctly signed with the exception of the unemployment differential. In the short run, in sharp contrast to Gani's (1998) findings, political instability is consistently the most important det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 28 publications
(76 reference statements)
0
14
0
Order By: Relevance
“…Moreover, those studies which exist have reached mixed results about the effects of the coups on migration from Fiji. Gani and Ward (1995), focusing on skilled migrants, and Narayan and Smyth (2003) found that political instability was statistically significant, whereas Gani (1998) found that the coups were a statistically insignificant determinant of migration from Fiji to New Zealand.…”
Section: The Fiji Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, those studies which exist have reached mixed results about the effects of the coups on migration from Fiji. Gani and Ward (1995), focusing on skilled migrants, and Narayan and Smyth (2003) found that political instability was statistically significant, whereas Gani (1998) found that the coups were a statistically insignificant determinant of migration from Fiji to New Zealand.…”
Section: The Fiji Contextmentioning
confidence: 99%
“…Previous studies to include a similar variable have found the cost of migration to have a negative and statistically significant effect on migration. These include Brosnan and Poot (1987), who examine the determinants of trans-Tasman migration flows between Australia and New Zealand, and Narayan and Smyth (2003), who examine the reasons for migration from Fiji to New Zealand.…”
Section: Costs Of Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Reddy et al, 2004;Voigt-Graf et al, 2007). Extensive attention has also been given to the impact of remittances on social protection and migration intentions (Jimenez and Brown, 2013;Leeves, 2009;Kaitani, et al, 2011), political instability as a migration determinant (Narayan and Smyth, 2003) and human capital loss as an emigration cost (Reddy et al, 2004;Chandra, 2004). In other words, the existing literature centres around the patterns, intentions, benefits and costs of (skilled) migrations, with an emphasis on their development impacts.…”
Section: Introductionmentioning
confidence: 99%
“…This was reflected in the large exodus of people to countries such as Australia, New Zealand and the United States. Over the 1987 to 1999 period, for instance, around 7 000 professionals and skilled workers emigrated from Fiji (Narayan and Smyth, 2003). Amid weakening democracy and mass skilled immigration, the growth performance of the Fijian economy over the last decade has been sluggish.…”
Section: Introductionmentioning
confidence: 99%